Taxonomic revision of the ant genus Leptomyrmex Mayr (Hymenoptera: Formicidae) - Lucky, Andrea; Ward, Philip S. (Zootaxa, 2010)
The ants of the genus Leptomyrmex (Hymenoptera: Formicidae), commonly called ‘spider ants’, are distinctive members of the ant subfamily Dolichoderinae and prominent residents of intact wet forest and sclerophyll habitats in eastern Australia, New Caledonia and New Guinea. This revision redresses pervasive taxonomic problems in this genus by using a combination of morphology and molecular data to define species boundaries and clarify nomenclature. Twenty-seven Leptomyrmex species are recognized and are informally split into two groups: the macro-Leptomyrmex (21 species), and its sister group, the micro-Leptomyrmex (six species). Nine subspecies are elevated to species status: L. cnemidatus Wheeler 1915, L. geniculatus Emery 1914, L. melanoticus Wheeler 1934, L. nigriceps Emery 1914, L. rothneyi Forel 1902, L. ruficeps Emery 1895, L. rufipes Emery 1895, L. rufithorax Forel 1915 and L. tibialis Emery 1895. Nineteen new synonymies are proposed (senior synonyms listed first): L. cnemidatus Wheeler 1915 = L. erythrocephalus venustus Wheeler 1934 = L. erythrocephalus brunneiceps Wheeler 1934; L. darlingtoni Wheeler 1934 = L. darlingtoni fascigaster Wheeler 1934 = L. darlingtoni jucundus Wheeler 1934; L. erythrocephalus (Fabricius 1775) = L. froggatti Forel 1910 =4 · Zootaxa 2688 © 2010 Magnolia PressL. erythrocephalus mandibularis Wheeler 1915 = L. erythrocephalus unctus Wheeler 1934 = L. erythrocephalus clarki Wheeler 1934; L. fragilis (F. Smith 1859) = L. fragilis femoratus Santschi 1932 = L. fragilis maculatus Stitz 1938 = L. wheeleri Donisthorpe 1948; L. melanoticus Wheeler 1934 = L. contractus Donisthorpe 1947; L. niger Emery 1900 = L. lugubris Wheeler 1934; L. rufipes Emery 1895 = L. quadricolor Wheeler 1934; L. rufithorax Forel 1915 = L. erythrocephalus basirufus Wheeler 1934; L. tibialis Emery 1895 = L. nigriventris hackeri Wheeler 1934; L. varians Emery 1895 = L. erythrocephalus decipiens Wheeler 1915 = L. varians angusticeps Santschi 1929; L. wiburdi Wheeler 1915 = L. wiburdi pictus Wheeler 1915. Tools for identification of the macro-Leptomyrmex species include a revised species-level key based on the worker caste, keys to males in Australia and New Guinea, full descriptions of workers, images of known workers, males and queens, and illustration of male genitalia. Phylogenetic relationships among the macroand micro- Leptomyrmex species are discussed, as is the status of a putative fossil relative.